1990
DOI: 10.1002/ajmg.1320370133
|View full text |Cite
|
Sign up to set email alerts
|

Severe combined immunodeficiency syndrome associated with autosomal recessive familial multiple gastrointestinal atresias: Study of a family

Abstract: Hereditary multiple atresias involving the gastrointestinal tract from pylorus to rectum are the most unusual form of intestinal atresia; the type of inheritance was suggested to be autosomal recessive. The inheritance of the severe combined immunodeficiency syndrome can be autosomal recessive or X-linked. We report on 3 sibs with multiple-level intestinal atresias. One sib had severe combined immunodeficiency syndrome and clinical histories of the other 2 sibs strongly suggested a congenital immunodeficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1
3

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 13 publications
2
38
1
3
Order By: Relevance
“…Thus, MIA-CID was a common feature of the 6 patients, as previously reported for other cases (8). A postmortem pathology study revealed hypoplastic thymuses in D3 and E3 (respectively, onetenth and one-third of the thymus size of age-matched controls).…”
Section: Figuresupporting
confidence: 80%
“…Thus, MIA-CID was a common feature of the 6 patients, as previously reported for other cases (8). A postmortem pathology study revealed hypoplastic thymuses in D3 and E3 (respectively, onetenth and one-third of the thymus size of age-matched controls).…”
Section: Figuresupporting
confidence: 80%
“…A subgroup of MIA patients also have signs of combined immunodeficiency and are termed multiple intestinal atresia with combined immune deficiency (MIACI) (Moreno et al 1990). MIACI has been described in unrelated families of multiple ethnicities including Saudi, Slavic, Italian, Bosnian, and French-Canadian (Rothenberg et al 1995;Chen et al 2013).…”
Section: Activated Pi3k-delta Syndrome Is a Novel Immunodeficiency Camentioning
confidence: 99%
“…Bu mul tipl at re zi ti pin de kla sik tip 4 at re zi den fark lı ola rak me zen ter de fek ti gö rül mez. [2][3][4][5][6][7][8][9][10] Li te ratür de yak la şık ola rak 43 ol gu bil di ril miş tir. 10 Ula-şı la bi len li te ra tür ler de ka lıt sal bar sak at re zi li be bek le rin ai le geç mi şin de ak ra ba ev li li ği ol ma sı -na rağ men bi rin ci de re ce den ak ra ba ev li li ğin den do ğan kar deş ler de bar sak at re zi si ne bir li te ra tür de rast lan mış tır.…”
Section: Tar Tiş Maunclassified
“…9 Bu gün ço ğun luk la ka bul edi len gö rüş hasta lı ğın oto zo mal re se sif ge çiş li ol du ğu yö nün de dir. An cak has ta lı ğın ka lı tım şek li ile il gi li gö rüş bir liği ne va rı la ma mış ve he nüz has ta lı ğa ait spe si fik gen mu tas yo nu bu lu na ma mış tır.…”
Section: Tar Tiş Maunclassified
See 1 more Smart Citation